Finance and Development, September 2008. (Finance and Development; Finance and Development ;, 2008)
'Commodity Boom: How Long Will It Last?' asks how economies will fare after the record-high prices of key raw materials posted in recent months, which build on dramatic increases from their lows of 2000. The lead article warns that the impact on headline inflation levels might persist throughout 2008, even without further commodity price hikes. It urges policymakers to ensure efficient functioning of market forces at the global level, and to move swiftly to protect the poorest. Another article addresses the effects of climate change on agriculture, warning that farm production will fall dramatically-especially in developing countries-if steps are not taken to curb carbon emissions. Other articles on this theme argue that policies to reduce greenhouse gas emissions need not hobble economies, and that financial markets can help address climate change. 'People in Economics' profiles John Taylor; 'Picture This' says the global energy system is on an increasingly unsustainable path; 'Country Focus' spotlights South Africa; and 'Straight Talk' examines early warnings provided by credit derivatives. Also in this issue, articles examine China's increasing economic engagement with Africa, and the outsourcing of service jobs to other countries.